PENGARUH CORPORATE GOVERNANCE, LEVERAGE DAN KARAKTERISTIK EKSEKUTIF TERHADAP TAX AVOIDANCE (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2015) - Nailul Huda; M Rasuli; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of Corporate Governance, Leverage and Executive Characteristicson Tax Avoidance in Manufacturing Companies listed on the Indonesia Stock Exchange. The research data is secondary data in the form of the company's financial statements and annual reports of companies. While the population in this study are all Manufacturing Companies listed on the Indonesia Stock Exchange during 2013-2015. Selection of the sample using purposive sampling method in which the population of 127 selected according to criteria of a sample of 18 companies selected. The Data analysis tool used is regression panel data.The results of this study indicate that Corporate Governance is proxied by the Audit Committee does not affect the Tax avoidance with a probability value of 0.4562. Quality audits are also a proxy of corporate ngovernance affect the tax avoidance with a probability value of 0.0378. Leverage effect on tax avoidance with a probability value of 0.0195. Characteristics executive proxied by the companies did not affect the risk of tax avoidance with a probability value of 0.3184A probability value of this research is 0.3512. The coefficient of determination in the study of 0.35 indicates that 35% of the variations that occur in tax avoidance is influenced by corporate governance, leverage, characteristics of the executive and the remaining 65% is influenced by other variables not included in this study.Keyword : corporate governance, audit committees, audit quality, leverage, characteristics of the executive, the company's risk, tax avoidance